Effect of Sowing Period on Incidence of Sucking Pests on Pigeonpea Cajanus cajan (L.) Millsp. - J. D. Patel; D. R. Patel; Alok Shrivastav (International Journal of Economic Plants)
A field experiments were carried out at the College farm, N. M. College of Agriculture, Navsari Agricultural University, Navsari during Kharif 2015-16 to study the effect of sowing period on incidence of sucking pest of pigeonpea. The study revealed that the pigeonpea pod bug and cow bug population were significantly influenced by sowing period and cultivars. The significant lowest cow bug and pod bug population was observed during crop sown on 2nd fortnight of July, while the highest population was recorded during crop sown on 2nd fortnight of August, i.e late sowing. The interaction effect of sowing dates and varieties had non-significant influence on the cow bug population while, significant influence on the number of pod bug plant-1.